Geopark Development Analysis in Acquiring UNESCO Global Geopark Status - Supriono, Supriono; Pangestuti, Edriana; Allolinggi, Rahmat Putra (Graduate School, Universitas Brawijaya, 2025)
The Maros-Pangkep Geopark is one of the geoparks in Indonesia. Designated as part of the national Geopark in 2018, Maros-Pangkep Geopark is currently selected as one of the candidates to become part of the UNESCO Global Geopark. This study aims to investigate the development of the Maros-Pangkep Geopark in its pursuit of UNESCO Global Geopark status, including the factors that support and hinder its progress. This study employs qualitative methods, utilizing data collection techniques that include interviews, observation, and documentation. The results of this study indicate that (1) The development carried out by the Maros-Pangkep Geopark in obtaining UNESCO Global Geopark status is quite good but needs to be improved, especially in the condition of existing public facilities, (2) The supporting factors in the development of the Maros-Pangkep Geopark are natural resources, accessibility, public facilities, community resources and policies, managers, completeness of documents, and support, (3) Inhibiting factors in the development of the Maros-Pangkep Geopark due to the COVID-19 pandemic, lack of funds, lack of human resources, and low levels of education and understanding public.